2009
DOI: 10.1071/rd08172
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biotechniques in buffaloes (Bubalus bubalis): status, prospects and challenges

Abstract: The swamp buffalo holds tremendous potential in the livestock sector in Asian and Mediterranean countries. Current needs are the faster multiplication of superior genotypes and the conservation of endangered buffalo breeds. Recent advances in assisted reproductive technologies, including in vitro embryo production methodologies, offer enormous opportunities to not only improve productivity, but also to use buffaloes to produce novel products for applications to human health and nutrition. The use of molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 71 publications
0
29
0
Order By: Relevance
“…To our knowledge, this is the first report on molecular description of buffalo oocytes at the mRNA level. This would help to understand the apparently unresolved problems with buffalo reproduction shortcomings and compromised ART results in this species (Singh et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first report on molecular description of buffalo oocytes at the mRNA level. This would help to understand the apparently unresolved problems with buffalo reproduction shortcomings and compromised ART results in this species (Singh et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Late maturity, poor estrus expression, prolonged calving intervals, seasonal reproductive patterns and low conception rates directly affect the propagation of good germplasm in buffalo (Nandi et al, 2002;Drost, 2007). Although several ARTs have been demonstrated in this species, the overall success rates of these techniques remain low, thus constraining their widespread adoption (Singh et al, 2009). Delineating the exact cellular mechanism of oocyte function and identification of new genes in oocytes of this species would not only help to understand the buffalo oocyte biology better, but would also provide markers to study the oocyte competence phenomena in any species.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that utilizing a cell line having greater plasticity and proliferative capacity than adult [11,57], Applications in veterinary regenerative medicine [2], derivation of various cell types from naturally occurring pluripotent or iPS cells, developing cell lines/cell cultures for isolation and growth of viruses [9,31,32,41], conservation of genetic diversity through repopulation of endangered species/cells for cloning/transgenic and iPS cell production [39,54].…”
Section: Pursuit Of Fetal Stem Cell Research In Livestockmentioning
confidence: 99%
“…Second, progeny of stem cell division may lose capacity for self-renewal, and can either differentiate or enter into a series of terminal divisions, finally yielding an organized tissue. Besides unprecedented role in basic, developmental biological and biomedical science, the stem cell technology is emerging as promising area to enhance animal production and biodiversity conservation [54,67]. Literature clearly demonstrates that despite two decades of research on animal ES cells, the ''proven'' stem cell lines are not yet reported [61].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the availability of an easily accessible and reproducible cell source may greatly facilitate the development of stem cell-based tissue engineering and therapies for regenerative veterinary medicine. Present study was undertaken for isolation, characterization and differentiation of these cells from the AM of water buffalo, a mainstay of dairy, meat and agriculture in several countries across the globe (Nanda and Nakao 2003;Singh et al 2009;Yadav et al 2011). …”
Section: Introductionmentioning
confidence: 99%